Pengaruh Mutu Pelayanan, Promosi dan Etika Pemasaran Perbankan Syariah Terhadap Keputusan Bertransaksi oleh Nasabah Floating Customers: Studi Kasus pada Nasabah BSI di Kota Probolinggo Jawa Timur - Inayah, Sholehatul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The development of Islamic banking in Indonesia is currently experiencing a significant increase, this is indicated by a significant increase in customer decisions to finance in Islamic banking. However, despite the high increase in customer numbers, customer loyalty to Islamic banking is still quite low. Therefore, this study will discuss several variables related to the formation of decisions in transactions. This study aims to identify the effect of service quality, promotion and marketing ethics of Islamic banking on transaction decisions by floating customers. This study uses a quantitative descriptive method. The sample in this study were BSI customers in Probolinggo City, East Java. The sampling technique used was purposive sampling technique with a total sample of 154 samples. The data analysis technique used is Structural Equation Modeling and Partial Least Square (SEM-PLS) with analysis tools using Smart-PLS 4.0. The results of this study indicate that service quality has no effect on transaction decisions of floating customers, promotion has a significant positive effect on transaction decisions of floating customers, ethics has a significant positive effect on transaction decisions of floating customers.